Antimicrobial susceptibility patterns: a three-year surveillance study in a rehabilitation setting - Chaudhry, Liaqat Ali (Pan Afr Med J, 2016)
INTRODUCTION: To analyze the susceptibility patterns in a rehabilitation center. METHODS: This retrospective observational study was conducted between January 2011 and to January 2013 at Sultan Bin Abdulaziz Humanitarian City (SBAHC), Riyadh, Kingdom of Saudi Arabia. Number of the patients, specimen type, pathogen detected and antibiogram were entered in database for analysis using Inter System Track care software. RESULTS: A total of 4525 isolates were available from 5148 patients. Most (74%) of the isolates were from urine samples and were due to Eschericia coli (49.8%), Enterococcus faecalis (15%) and (Proteous mirabilis(9.49%). Of all the isolates, Eschericia coli was the commonest (49.8%) Gram negative organism, while(Stahylococcus aureus was the commonest (51%) among Gram positive organisms. The most effective antibiotics against Pseudomonas aeroginosa were ciprofloxacin and gentamicin. Meropenem shows excellent activity against Gram negative bacteria. Methicillin resistant Staphylococcus aureus (MRSA) was susceptible to Vancomycin and Rifampicin in 97% and 85% cases. CONCLUSION: A high incidence of urinary tract infections caused by Eschericia coli, Enterococcus faecalis and Proteous mirabilis was reported. Staphylococcus aureus was the commonest pathogen isolated from infected bed sores.